2018
DOI: 10.1038/s41586-018-0084-4
|View full text |Cite|
|
Sign up to set email alerts
|

Subepithelial telocytes are an important source of Wnts that supports intestinal crypts

Abstract: Tissues with rapid cellular turnover, such as the mammalian hematopoietic system or the intestinal epithelium, are dependent upon stem and progenitor cells, which through proliferation provide differentiated cells to maintain organismal health. Stem and progenitor cells, in turn, are thought to rely upon signals and growth factors provided by local niche cells to support their function and self-renewal. Several cell types have been proposed to provide the signals required for the proliferation and differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
564
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(599 citation statements)
references
References 32 publications
33
564
2
Order By: Relevance
“…The difference between the ileum and colon regarding the pattern and number of ICCs and TCs, around and within the ganglia, could possibly be explained by the difference in motility between the small and large bowel . The TCs have an important role in the organization and control of the extracellular matrix, structural support, intercellular communication and creation of the environment . Furthermore, TCs contribute to the regulation of the Wnt pathway in regeneration and through toll‐like receptors in immunoregulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the ileum and colon regarding the pattern and number of ICCs and TCs, around and within the ganglia, could possibly be explained by the difference in motility between the small and large bowel . The TCs have an important role in the organization and control of the extracellular matrix, structural support, intercellular communication and creation of the environment . Furthermore, TCs contribute to the regulation of the Wnt pathway in regeneration and through toll‐like receptors in immunoregulation .…”
Section: Discussionmentioning
confidence: 99%
“…TCs have been localized in several other organs as well . Several investigations have suggested that TCs and PDGFRα‐positive cells influence the intestinal motility, among many other functions …”
Section: Introductionmentioning
confidence: 99%
“…In greater detail, Olga simionescu and colleagues demonstrated that telocytes maintained in close contact with mast cells, macrophages and mononuclear cells by their long telopode and an apoptotic telocyte with condensed chromatin has been found in the vicinity of a dendritic cell in psoriasis . Although a few studies have reported the function of telocytes, little is known about the relationship between telocytes and other cells. We found that the level of iNOS was significantly increased after TLR2 activation (Figure C,), suggesting that activated telocytes had enhanced the ability of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, signals are derived from specialized niche cells that control stem cell quiescence for long periods of time, regulate stem cell self-renewal, or guide their differentiation into one or more lineages of the respective tissue. Neighboring niche cell types and their signals have been identified in several tissues such as bone marrow (Wei and Frenette, 2018), intestine (Shoshkes-Carmel et al, 2018), brain (Falk and Götz, 2017), lung (Lee et al, 2017) and skin (Ge and Fuchs, 2018; Sennett and Rendl, 2012). But a detailed understanding of the molecular controls of niche fate specification during embryonic development remains limited.…”
Section: Introductionmentioning
confidence: 99%